Excessive daytime sleepiness and risk for obstructive sleep apnea in the public transport drivers - Łukasz Minarowski; Sylwia Chwieśko-Minarowska; Marcin Czaban; Magdalena Mickiewicz; Natalia Kozakiewicz; Anna Kuryliszyn-Moskal; Elżbieta Chyczewska (Nofer Institute of Occupational Medicine, 2015)
Background: Obstructive sleep apnea (OSA) is a set of symptoms related to the increased upper airways resistance during sleep (due to pharyngeal walls collapse) leading to intermittent airflow obstruction in the lungs. One of the most severe OSA symptoms is excessive daytime sleepiness. Sustained daytime sleepiness may impair cognitive functions and thus influence the everyday functioning of affected person. Material and Methods: The aim of the study was to prospectively assess excessive daytime sleepiness and the risk for OSA in municipal bus drivers. The study was performed in a group of 103 men. The anonymous survey comprised Epworth Sleepiness Scale (ESS) for daytime sleepiness assessment and STOP-Bang Questionnaire (SBQ) for OSA risk assessment. Results: In 43 (42%) respondents OSA risk was assessed as low, while moderate and high risk was observed in 55 (53%) and 5 (5%) drivers, respectively. Severe daytime sleepiness correlated positively with ESS results (r = 0.32; p < 0.05). In drivers with high OSA risk revealed in SBQ no correlation with high ESS was observed. Conclusions: In drivers with moderate and high OSA risk a sleep medicine specialist consultation with a consecutive diagnostic procedures is necessary. STOP-Bang Questionnaire and ESS are the fast tools to identify patients at increased risk for OSA. Med Pr 2015;66(5):679-685